MEMBANGUN KERUKUNAN MASYARAKAT BEDA AGAMA MELALUI INTERAKSI DAN KOMUNIKASI HARMONI DI KECAMATAN SUKARAME - Wulandari, Vera (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2020)
This research tries to take the pattern of interaction between people of different religions in the sub-district of Soekarno, Bandar Lampung. The paradigm in this research is qualitative by using sociology and symbolic interaction. The data was collected by means of interview techniques, observation and documentation study. The results showed that the harmony of life for people of different religions in the sub-district of Soekarno-Hatta was built through interaction and communication of harmony that respected each other, respected each other, gave mutual tolerance and did not touch on religious issues in people's lives. Other supporting factors are: first, high awareness from the community of the importance of religious harmony which has been instilled since childhood by their predecessors; second, the growth of a spirit of nationalism in people's lives; and third, the existence of kinship ties resulting from previously interfaith marriages.